Perceptions of Teachers about the Role of Parents in Developing Reading Habits of Children to Improve their Academic Performance in Schools - Jamila Bano; Zahra Jabeen; Sadruddin Bahadur Qutoshi (Journal of Education and Educational Development, 2020)
This study aimed to explore teachers’ perceptions about parental role in developing reading habits of children to improve their academic achievement. The study was conducted in one of the private schools of Gilgit city situated in the Northern part of Pakistan. Using a case study approach to research within the qualitative design, semi-structured interviews were used for data collection, which enabled the researchers in capturing qualitative experiences, opinions, beliefs and perceptions of purposefully selected research participants. The data were analyzed using thematic analysis approach and emerging themes were represented in the form of figures to provide a clear understanding. The study confirmed that reading habits, for example, out of school reading and reading for pleasure, have influenced academic performance and parental role is pivotal in developing children’s interest in reading because healthy reading activities can help them to develop critical thinking and analytic skills. This could also develop their vocabulary to a great extent. Consequently, children exhibit improvement in their overall academic performance. The findings confirmed that if parents focused on reading improvement of their children in early ages, they could better develop reading as a routine activity. The study recommended that parents should play an active role in developing attitude towards reading by providing reading materials and creating a reading friendly environment at home.
Keywords: academic achievement; parental role; reading environment; reading habits